Ferroelectric polarization reversals in C2N/α-In2Se3 van der Waals heterostructures: a conversion from the traditional type-II to S-scheme - Zhong, Yongle (Frontiers in Chemistry, 2023)
Ferroelectric substances characterized by inherent spontaneous polarization can boost photocatalytic efficiency by facilitating the separation of photogenerated carriers. Nevertheless, conventional photocatalysts with perovskite-class ferroelectricity are generally constrained by their 3D arrangement, leading to less accessible active sites for catalysis and a smaller specific surface area relative to a 2D layout. In our research, we developed a 2D ferroelectric heterostructure consisting of C2N/α-In2Se3. We conducted first-principle calculations on the 2D C2N/α-In2Se3 heterostructure with varying out-of-plane ferroelectric polarization directions, specifically, C2N/α-In2Se3 (I) and C2N/α-In2Se3 (II) heterostructures. Our findings revealed that upon reversing the ferroelectric polarization of the 2D α-In2Se3 layer in the heterostructures, the heterostructure transitioned from the conventional type-II (C2N/α-In2Se3 (I)) to an S-scheme (C2N/α-In2Se3 (II)). The S-scheme heterostructure (C2N/α-In2Se3 (II)) demonstrated a high optical absorption rate of 17% in visible light, marking it as a promising photocatalytic material. This research underscores the significance of ferroelectric polarization in facilitating charge transfer within heterogeneous structures and provides theoretical perspective for developing enhanced S-scheme photocatalysts.